Captopril Treatment in Rheumatic Heart Disease with Congestive Heart Failure A Preliminary Report - Hardiman Sastrosubroto; Santosa Soeroso; Eriyati Indrasanto (Paediatrica Indonesiana, 1989)
A small scale controlled trial of captopril (ACE inhibitor) was conducted in 8 children with congestive heart failure due to rheumatic mitral regurgitation with or without mild mitral stenosis. The age of the patient ranged from 5.5 to 13 years (mean 9,3 years). Four children, served as control group, received digitalis and diuretics as standard treatment; while the other 4 children also received 2 x 12,5 mg of captopril in addition to standard treatment. The effect of both regimens were measured by usingchanges of left ventricular function as seen on the echocardiogram performed before treatment, and then 3, 7 and 14 days thereafter. Definite conclusion cannot be made because of the small number of patients; but it is apparent that some improvements of left ventricular functions in the captopril group were more evident when compared with that of the control group of standard treatment.Side effects of captopri/ were not found.